Intervention methodologies for architectural reuse: a systematic review towards sustainability - Salvatierra-Canova, Milagros Grace; Terrones-Valera, Angelyn Melanie Maithe; Cruzado-Palacios, María Delia; Avalos-Gámez, Leogilda (LACCEI, 2025)
The reuse of architectural infrastructure is essential for heritage conservation, urban sustainability and resource optimization; however, it faces challenges such as technological obsolescence, lack of planning and inadequate regulations. Therefore, through the PRISMA method, a systematic review of research published between 2020 and 2025 in the Scopus and Web of Science databases was carried out, through which, from a total of 6,892,183 articles, 40 relevant studies were selected, with a higher concentration of publications in Europe and America. In this sense, various intervention methodologies were identified, among which adaptive reuse, life cycle assessment (LCA), energy conservation strategies, management models for rehabilitation, multi-criteria assessment methods (MCDM) and structural and seismic approaches stand out. Of these, adaptive reuse is considered the most effective strategy, as it reduces the environmental impact and improves the performance of buildings in terms of functionality and energy efficiency. In conclusion, the research findings underline the growing importance of these methodologies in sustainable urban development and the preservation of the built environment.